Optimizing Customer Engagement: Agile CRM Development In The Restaurant Industry - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This study examines implementing Agile methods in Customer Relationship Management (CRM) development for the restaurant industry, focusing on optimizing customer engagement. The development stages include system requirement analysis, application development using Extreme Programming (XP) method, and functional testing and user evaluation. The study aims to enhance operational efficiency and customer interaction in the context of the restaurant business. The Agile method emphasizes team collaboration, rapid iterations, and continuous testing to produce an adaptive and responsive CRM application. The user evaluation results provide valuable feedback for system improvement and quality enhancement before the official launch. This research significantly contributes to information technology development and supports more effective and competitive business strategies in the restaurant industry.